Duration and intensity of primary molt in two neotropical grasslands Passerines - Miguel Moreno Palacios; Sergio Losada Prado; María Ángela Echeverry Gálvis (Caldasia)
Description of patterns and mechanics of bird molt have permitted understanding and have clarified temporal and spatial dynamics in the life cycles of several temperate species. Few studies evaluate these aspects in Neotropical birds, which hinders their discussion in functional and evolutionary contexts. Here we compare primary molt duration and intensity of flight feather molt in two Neotropical passerine species, Blue-black Grassquit and Gray Seedeater. The study took place north of the department of Tolima-Colombia. Birds were captured and were marked with colored bands. Molt duration estimates follow Pimm’s and Rohwer and Wang’s methods, while molt intensity was evaluated using Rohwer’s proposal. Primary molt duration of Blue-black Grassquit was between 59 days (CI 95 % = 48–74) and 80 days (CI 95 % = 64–96), while the duration for Gray Seedeater was between 80 days (CI 95 % = 66–105) and 100 days (CI 95 % = 75–124). Estimates were consistent with those of other Neotropical Passerines with similar body mass, with a longer duration than that of temperate birds, evidence in favor of the hypothesis of slower pace of life in tropical birds. Method by Rohwer and Wang presents methodological advantages that would permit evaluating molt duration in species with low capture rates, suspended molts, or low molt synchrony between individuals. Molt intensity was higher in Gray Seedeater (13 feathers) than Blue-black Grassquit (9.3 feathers), and both were greater compared with other Passerines, which may represent an adaptive response to specific ecological pressures.